Nutrient management productivity and nutrient-use efficiency in floodplain soils under maize (Zea mays)-wheat (Triticum aestivum) cropping - SAINI, SAT PAL; SINGH, PRITPAL; BRAR, B S (The Indian Journal of Agricultural Sciences, 2019)
An experiment was conducted to evaluated the impacts of inorganic fertilizers applied either alone or conjointly with farmyard manure (FYM) on yield, nitrogen (N), phosphorus (P) and potassium (K)-use efficiency and economics of maize (Zea mays L.)-wheat (Triticum aestivum L.) cropping in floodplain soils. Farmers' field experiments were conducted at three locations with five treatments: absolute control (CK), farmers' practice (FP), recommended NPK (NPK), NPK+FYM and FP+FYM in maize and the same treatments were applied without FYM in wheat. Grain yield and nutrient (N, P and K) uptake increased significantly (P